1960
DOI: 10.1113/expphysiol.1960.sp001471
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Measurement, in Unanæsthetized Rats, of Intestinal Transport and Fat Absorption From the Lumen

Abstract: A test meal containing emulsified coconut oil mixed with water soluble polyethyleneglycol (PEG) of high mol. wt. was given to rats by gastric intubation. At intervals up to 5 hr. after the meal, rats were killed and the amounts of PEG and fat recoverable from the stomach, small intestine and coecum were measured. PEG was not absorbed from, nor broken down in, the intestine and left the stomach at the same rate as the emulsified fat. It was, therefore, a suitable reference substance. With a test meal of constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0

Year Published

1963
1963
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(29 citation statements)
references
References 1 publication
5
24
0
Order By: Relevance
“…3 and 7). These observations are in agreement with those of Aberdeen et al 17 ) They compared the ratio of fat to polyethyleneglycol in successive segments of the small intestine of rats and found that fat was absorbed chiefly in the distal half.…”
Section: Discussionsupporting
confidence: 92%
“…3 and 7). These observations are in agreement with those of Aberdeen et al 17 ) They compared the ratio of fat to polyethyleneglycol in successive segments of the small intestine of rats and found that fat was absorbed chiefly in the distal half.…”
Section: Discussionsupporting
confidence: 92%
“…(1960) and verified by us, may be that the rinsing of the space between the villi is inefficient. When longer absorption times are used, the solution reaches the lower parts of the intestine where the villi are not so numerous, and consequently more of the polyethylene glycol is recovered (Aberdeen et al 1960). By homogenization of the intestine this difficulty is overcome.…”
mentioning
confidence: 99%
“…While apoA-V is well-demonstrated to profoundly regulate fasting plasma TG in both mice (20,49,15,49,61,70,64) and humans (1,14,23,32,21), little is known about the contribution of apoA-V to lipid absorption and postprandial TG metabolism. Results from apoA-V transgenic mice (15) and adenovirus-mediated gene transfer experiments to mice (49) suggest that apoA-V suppresses the surge in plasma TG after a lipid meal.…”
Section: Discussionmentioning
confidence: 99%
“…A lipid emulsion was prepared by dissolving triolein {labeled with [9, H(N)]triolein}, cholesterol {labeled with [1,[2][3][4][5][6][7][8][9][10][11][12][13][14] C(N)]cholesterol}, and egg phosphatidylcholine in chloroform, which was then evaporated under nitrogen gas. The chloroform-free mixture was emulsified with 19 mM sodium taurocholate (NaTC) in phosphate-buffered saline (PBS) at pH 6.4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation